γδ-T cells promote IFN-γ–dependent Plasmodium pathogenesis upon liver-stage infection - Ribot, Julie C. (2019)
Cerebral malaria (CM) is a major cause of death due to Plasmodium infection. Both parasite and host factors contribute to the onset of CM, but the precise cellular and molecular mechanisms that contribute to its pathogenesis remain poorly characterized. Unlike conventional αβ-T cells, previous studies on murine γδ-T cells failed to identify a nonredundant role for this T cell subset in experimental cerebral malaria (ECM). Here we show that mice lacking γδ-T cells are resistant to ECM when infected with Plasmodium berghei ANKA sporozoites, the liver-infective form of the parasite and the natural route of infection, in contrast with their susceptible phenotype if challenged with P. berghei ANKA-infected red blood cells that bypass the liver stage of infection. Strikingly, the presence of γδ-T cells enhanced the expression of Plasmodium immunogenic factors and exacerbated subsequent systemic and brain-infiltrating inflammatory αβ-T cell responses. These phenomena were dependent on the proinflammatory cytokine IFN-γ, which was required during liver stage for modulation of the parasite transcriptome, as well as for downstream immune-mediated pathology. Our work reveals an unanticipated critical role of γδ-T cells in the development of ECM upon Plasmodium liver-stage infection.